Reliability, maintainability and risk : practical methods for engineers - Smith, David J. 1943 June 22- (Butterworth-Heinemann, an imprint of Elsevier, 2022)
Reliability, Maintainability and Risk: Practical Methods for Engineers, Tenth Edition has taught reliability and safety engineers techniques to minimize process design, operation defects and failures for over 40 years. For beginners, the book provides tactics on how to avoid pitfalls in this complex and wide field. For experts in the field, well-described, realistic and illustrative examples and case studies add new insights and assistance. The author uses his more than 40 years of experience to create a comprehensive and detailed guide to the field, while also providing an excellent description of reliability and risk computation concepts. The book is organized into many parts, covering reliability parameters and costs, the history of reliability and safety technology, a cost-effective approach to quality, reliability and safety, how to interpret failure rates, a focus on the prediction of reliability and risk, a discussion of design and assurance techniques, and much more.
Keywords: Reliability (Engineering); Maintainability (Engineering); Engineering design.; elektronické knihy; electronic books